Prove: So what I have is: now I'm not quit sure that this is right
Follow Math Help Forum on Facebook and Google+
Hello, Originally Posted by lllll Prove: So what I have is: now I'm not quit sure that this is right Hmm you have to separate the cases when and More simply : and that's the exact definition of
The sequence of formulas is as follows: Lim =0 <====> [ε>0------> ( kεN & ( n k--------> ))] <=====> [ε>0------> ( kεN & ( n k--------> ))] <======> Lim =0 As n-----> OO ( infinity). The above equivalences hold because: <=====> , since: = ,
View Tag Cloud